Effectiveness of low level laser therapy versus cryotherapy in cancer patients with oral mucositis: Systematic review and network meta-analysis. (April 2021) - Lai, Chih-Chin; Chen, Shiau-Yee; Tu, Yu-Kang; Ding, Yu-Wei; Lin, Jiu-Jenq
Graphical abstract: Highlights: This network meta-analysis compares the efficacy of non-pharmacological management of the occurrence of severe, moderate and none/mild oral mucositis. Selected RCTs compared combined cryotherapy and laser, laser alone, cryotherapy alone and usual care in cancer patients. SUCRA values were used to identify the best possible therapy in the network meta-analysis. Combined cryotherapy and laser are the most effective treatment for severe and moderate OM. Abstract: Objective: The purpose of this network meta-analysis was to analyze the relative effects of low level laser therapy (LLLT) and/or cryotherapy in cancer patients with oral mucositis (OM). Methods: This literature search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines using MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), and the Physiotherapy Evidence Database (PEDro) up to 2020. Only randomized control trials which involved comparisons of groups receiving the interventions of combined cryotherapy and LLLT, LLLT, cryotherapy and usual care (the control group) in patients with cancer were eligible for inclusion. The effect sizes are presented as odds ratios for the occurrence of severe, moderate and none/mild OM. The mixed treatment comparison was conducted using generalized linear mixed models to analyze the direct and indirect comparisons of interventions. The critical appraisal was assessed using Cochrane Collaboration's tool. Heterogeneity between studies was assessed using I 2 statistics, and publication bias was evaluated by constructing a funnel plot. Results: Twenty-six randomized controlled trials with a total enrollment of 1830 cancer patients with OM were included. The outcome of none/mild OM is desirable, and odds ratios of more than 1 favor the intervention group. Moderate and severe OM are defined as adverse outcomes, and ORs less than 1 favor the intervention group. The treatment effects of the combined cryotherapy and LLLT were better than those of usual care for none/mild and severe OM (ORs = 106.23 [95% CI = 12.15 to 929.17] and 0.01 [95% CI = 0 to 0.57], respectively). Treatment effects with cryotherapy alone and LLLT alone were better than those with usual care for none/mild and severe OM (ORs = 3.13 [95%CI = 1.56 to 6.27]; ORs = 7.56 [95%CI = 3.84 to 14.88] and 0.25 [95%CI = 0.11 to 0.54]; ORs = 0.13 [95%CI = 0.07 to 0.24], respectively). Nevertheless, for patients with none/mild OM, treatment effects with combined use of cryotherapy and LLLT were better than those with only LLT or cryotherapy (ORs = 14.06 [95%CI = 1.79 to 110.30] and 33.95 [95%CI = 3.50 to 329.65], respectively). For patients with moderate OM, treatment effect did not reach statistical significance among comparisons. The limitations include the wide variability in treatment protocols and the non-uniform outcome measurements across the studies examined. Conclusion: Compared with no intervention, the treatment effects of combined cryotherapy and LLLT, laser alone, and cryotherapy alone are beneficial for the reduction of severe OM. There is no difference in treatment effects among cryotherapy and/or LLLT intervention in cancer patients with moderate OM. Results of this study provide an implicative basis for LLLT and cryotherapy as viable interventions that can significantly improve severe OM.